Organelles Ca2+ redistribution contributes to cadmium-induced EMT of renal cancer cells through p-cPLA2-mediated arachidonic acid release - Jie Gu; Jiacheng Ruan; Chuanzhi Guo; Zehua Li; Huilin Fu; Yimin Xie; Hebing Xie; Xun Gong; Haifeng Shi (Ecotoxicology and Environmental Safety)
Cadmium ion (Cd2+) is a non-essential metal that can increase cancer risk, including potentially renal cell carcinoma (RCC), though this link is not definitive. Cd2+ exposure impairs fatty acid metabolism in the kidneys, particularly affecting arachidonic acid (AA) levels, which are crucial for health. Previous studies have suggested that Cd2+-altered the AA metabolism associates with renal dysfunction. However, the role and mechanism of Cd2+-regulated AA source in promoting RCC progression are still unclear. This study aims to investigate how Cd2+ exposure affects AA levels in renal cancer cells and its role in promoting cell migration. Cd2+ exposure increases AA levels through cPLA2-mediated release. It also induces calcium ion (Ca2+) redistribution from the endoplasmic reticulum (ER) to mitochondria, activating the p38 MAPK/cPLA2 signaling pathway, and epithelial-mesenchymal transition (EMT) of Caki-1 cells. Cd2+-induced ER Ca2+ release, p38 MAPK/cPLA2 signaling activation, AA levels, and EMT of Caki-1 cells were effectively reversed by siRNA knockdown of IP3R. Both exogenous AA treatments and Cd2+-induced AA metabolite PGD2 promoted EMT and cell migration of Caki-1 cells. This study highlights Cd2+’s impact on fatty acid metabolism and organelle function in renal cancer cells, identifying potential therapeutic targets for RCC.